1997
DOI: 10.1001/archinte.1997.00440350031003
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Criteria for Determining Potentially Inappropriate Medication Use by the Elderly

Abstract: This study updates and expands explicit criteria defining potentially inappropriate medication use by the elderly. Additional goals were to address whether adverse outcomes were likely to be clinically severe and to incorporate clinical information on diagnoses when available. These criteria are meant to serve epidemiological studies, drug utilization review systems, health care providers, and educational efforts. Consensus from a panel of 6 nationally recognized experts on the appropriate use of medication in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
317
0
25

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,039 publications
(343 citation statements)
references
References 0 publications
1
317
0
25
Order By: Relevance
“…The most commonly inappropriately prescribed medication was chlordiazepoxide, diazepam (27.78%) and meprobamate (13.89%). Other study reveal values similar to those identified in relation to the use of potentially inappropriate medication (Beers, 1991;Beers, 1997;Stuch et al, 1994;Pardo et al, 2003;Bandrés et al, 2008), which exposes the elderly to unnecessary risks such as adverse effects of a worsening of the quality of life, increased hospitalizations and increased health spending (Jano et al, 2007).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The most commonly inappropriately prescribed medication was chlordiazepoxide, diazepam (27.78%) and meprobamate (13.89%). Other study reveal values similar to those identified in relation to the use of potentially inappropriate medication (Beers, 1991;Beers, 1997;Stuch et al, 1994;Pardo et al, 2003;Bandrés et al, 2008), which exposes the elderly to unnecessary risks such as adverse effects of a worsening of the quality of life, increased hospitalizations and increased health spending (Jano et al, 2007).…”
Section: Discussionsupporting
confidence: 57%
“…In the same way, amitriptyline and chlordiazepoxide, due to their anticholinergic and sedating properties, are not the best choice for elderly patients. Meprobamate produces sedation relatively easily, that is why all the drugs were inadequately used in the patients of the sample (Beers, 1997;Fick et al, 2003;Pardo et al, 2003;Bandrés et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…General prescribing criteria for older adults do not specifically consider the particularities of a progressive, life‐limiting nature of dementia 45, 46, 47, 48, 49. We anticipated that this project would generate a list of appropriate and inappropriate medications for managing co‐morbidities in dementia, similar to other existing explicit prescribing criteria in older people such as the Beers and STOPP/START criteria 60, 61.…”
Section: Discussionmentioning
confidence: 99%
“…Medication management decisions for people with dementia are often based on data collected in younger adults or peers, which may not be generalisable or relevant to this population. The existing explicit prescribing criteria developed for older people do not account for the additional complexities of dementia or its life‐limiting nature 45, 46, 47, 48, 49. Consensus‐based guidance specifically for people with dementia would assist clinicians with decision‐making in this population 50, 51.…”
Section: Introductionmentioning
confidence: 99%
“…141 Updated versions include recommendations for community-dwelling older adults. 60,143 The criteria were developed based on recommendations from nationally recognized experts in geriatric care, clinical pharmacology, and psychopharmacology, by using a modified Delphi method. 60,[141][142][143] Investigators compiled a list of drugs that are potentially inappropriate in any patient older than 65 years and a list of drugs that should be used cautiously based on certain diseases or conditions.…”
Section: Population Assessmentsmentioning
confidence: 99%